Development of self-charging unmanned aerial vehicle system using inductive approach - Khairul Kamarudin Hasan; Shakir Saat; Yusmarnita Yusop; Md Rabiul Awal (Institute of Advanced Engineering and Science, 2022)
This paper presents an alternative approach to power up unmanned aerial vehicle (UAV) system using inductive approach. The main issue of utilizing UAV in any application especially in precision agriculture is the lifetime of the battery. This limits the flight time of the UAV which makes the system is unable to be efficiently applied for precision agriculture purpose. Hence, this paper proposes a new approach of powering UAV system by using so called inductive power transfer (IPT) technology. Through this approach, the system can be powered up wirelessly with no physical link in between transmitter and receiver. To be specific, class E inverter circuit has been designed together with impedance matching circuit to ensure higher efficiency is obtained. Finally, a prototype of IPT system for powering up the UAV system was successfully developed, which is able to transmit 23.32 W of power at 1 MHz operating frequency from 12 V input supply. The system achieved up to 95.73% efficiency.